2014
DOI: 10.5430/wje.v4n5p11
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Quality, Learning Satisfaction, and Academic Performance among Hospitality Students in Taiwan

Abstract: The purpose of this study is to examine the effect of the teaching quality of culinary arts teachers and student learning satisfaction on the academic performance of hospitality students. This study surveys the students in hospitality departments at universities in Taiwan. A total of 406 (81.2%) valid questionnaires were received. Research results show that there is a significant positive correlation between teaching quality of teachers and the learning satisfaction of students, between teaching quality of tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
0
22
0
5
Order By: Relevance
“…Studies in Mathematics education have examine the relationship between students' academic performance and their teacher's academic qualification, and in most case the teachers academic qualification and students' performance are positively correlated [27]. The study by [4,22,30] also had slightly similar results of positive correlation between student academic performance and teachers' qualification although extremely greater percentage of the student had viewed teacher's qualification to have negatively correlated with the student academic performance.…”
Section: Teachers' Self-efficacy and Certificationmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies in Mathematics education have examine the relationship between students' academic performance and their teacher's academic qualification, and in most case the teachers academic qualification and students' performance are positively correlated [27]. The study by [4,22,30] also had slightly similar results of positive correlation between student academic performance and teachers' qualification although extremely greater percentage of the student had viewed teacher's qualification to have negatively correlated with the student academic performance.…”
Section: Teachers' Self-efficacy and Certificationmentioning
confidence: 93%
“…The less academic achievement, according to the studies [20][21][22] can be mastered if quality of teaching is practiced by teachers. In this case the teachers teaching methods should be examined to maximized learning for all students.…”
Section: Teachers' Self-efficacy and Certificationmentioning
confidence: 99%
“…Issues of higher education in global environment have been widely examined, while how international students adjust socially, culturally, and economically should be more investigated in addition to academic related aspects. Previous studies (Eze & Inegbedion, 2015;Lee, 2014;Li, Chen, & Duanmu, 2010;Martirosyan, Hwang, & Wanjohi, 2015) have addressed that international students often face difficulties that include, i) lack of language proficiency especially in English-speaking countries; ii) academic conditions such as courses, teaching and assessment methods, unfamiliar academic systems, and communications (Joo, Chung, Lee, & Han, 2011;Ko & Chung, 2014;Tamaoka, Ninomiya, & Nakaya, 2013) iii) social issues associated with various kinds of relationships and living environments in the host societies (Alharbi & Smith, 2018, Lee, 2014; iv) cultural issues such as culture shock in their adaptation process to the local culture (Lee, 2014;Wang, 2004); v) financial problems based on expensive living expenses or unstable funding resources (Banjong, 2015;Lee, 2017); and vi) psychological problems from homesickness or loneliness (Alsahafi & Shin, 2017;Banjong, 2015;Sandhu & Asrabadi, 1994). Additionally, Wan, Chapman, and Biggs (1992) acknowledged that the psychological problems such as stress the students gain from their academic experiences can negatively impact students" academic achievement and satisfaction with the experiences in cultural exchange.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Academic factors are the factors related to the school and learning environment such as curriculum, courses, school system, and academic supervisor. Ko and Chung (2014) examined the relationship between quality of class, students" satisfaction, and academic performance of the students and found that there were correlation between class quality and students" satisfaction and between class quality and the students" academic performance. Joo, Chung, Lee, and Han (2011) confirmed that the usefulness of the education contents is correlated with academic performance of the students.…”
Section: Academic Factorsmentioning
confidence: 99%
“…Essas evidências não são limitadas apenas ao ensino fundamental ou médio. Diversos trabalhos (Tassoin, 2000;Haidet & Stein, 2006;Mazer, Murphy & Simonds, 2007;Bardagi & Hutz, 2012;Ko & Chung, 2014;Noland & Richards, 2014;Kember, Chan & Webster, 2015) demonstram que também no ensino superior a importância da interação entre professor e alunos é fundamental para o bom desenvolvimento do profissional. Por outro lado, há um grande desafio no que concerne ao desenvolvimento de um modelo teórico e conceitual para que se compreenda melhor essa relação, através de pesquisas que possam capturar os fenômenos complexos, dinâmicos e de contexto específico sob investigação (Hagenauer & Volet, 2014).…”
Section: Contextualizaçãounclassified